Undergraduate Medical Education: Lifestyle Medicine Curriculum Implementation Standards. Issue 5 (September 2021) - Trilk, Jennifer L.; Worthman, Shannon; Shetty, Paulina; Studer, Karen R.; Wilson, April; Wetherill, Marianna; Whelan, Lori; Bansal, Shipra; Alexander, Megan; Frates, Beth; Cramer, Sylvia; Rea, Brenda
Lifestyle medicine (LM) is an emerging specialty that is gaining momentum and support from around the world. The American Medical Association passed a resolution to support incorporating LM curricula in medical schools in 2017. Since then, the American College of Lifestyle Medicine Undergraduate Medical Education Task Force has created a framework for incorporating LM into medical school curricula. This article provides competencies for medical school LM curriculum implementation and illustrates how they relate to the Association of American Medical College's Core Entrustable Professional Activities and the LM Certification Competencies from the American Board of Lifestyle Medicine. Finally, standards are presented for how medical schools may receive certification for integrating LM into their curriculum and how medical students can work toward becoming board certified in LM through an educational pathway.